Sustainability in a digital world : new opportunities through new technologies - Osburg, Thomas (Springer, 2017)
This book offers a comprehensive introduction to the different emerging concepts in the innovative area of sustainability and digital technology. More than 20 leading thinkers from the fields of digitalization, strategic management, sustainability and organizational development share clearly structured insights on the latest developments, advances and remaining challenges concerning the role of sustainability in an increasingly digital world. The authors not only introduce a profound and unique analysis on the state-of-the art of sustainability and digital transformation, but also provide business leaders with practical advice on how to apply the latest management thinking to their daily business decisions. Further, a number of significant case studies exemplify the issues discussed and serve as valuable blueprints for decision makers.
Keywords: Digital media -- Social aspects.; Information technology -- Social aspects.; Information society.; Sustainable development.; elektronické knihy; electronic books